Adaptive aeroservoelastic mode stabilization of flexible airbreathing hypersonic vehicle. (August 2019) - Piao, Minnan; Zhang, Youan; Sun, Mingwei; Yang, Zhihong; Wang, Zenghui; Chen, Zengqiang
The statically unstable airbreathing hypersonic vehicle requires a high-bandwidth controller to control the instability, which results in intricate interactions among the aerodynamics, the low-frequency structural modes, and the flight control system. Especially, the structural frequencies are uncertain and time-varying, which further raises the difficulty of controller design. In this paper, two adaptive aeroservoelastic mode stabilization methods are proposed. First, the condition of phase stabilization is given under the linear active disturbance rejection control framework to realize the self-stabilization of the flexible modes. Then, an adaptive notch filter, which employs the lattice type structure and the fast-recursive square root algorithm, is presented. Both methods can achieve the adaptive vibration suppression and extend the control bandwidth. Simulation results demonstrate the effectiveness of the proposed approach.